Biodegradação de atrazina estimulada por Saccharomyces cerevisiae e palha de milho - Toller, Nathalia Marcon (2019)
In view of the various environmental and health problems that the increasing use of pesticides is causing, it is necessary to optimize techniques that aim at their rapid degradation. Atrazine (2-chloro-4-ethylamino-6-isopropylamino-striazine) is a herbicide widely used in weed control, especially in maize and sugarcane crops. In this sense, the present work aims to study the degradation of atrazine herbicide using the bioaumento technique, residual yeast biomass from the brewing industry and addition of corn straw in two soils, one with atrazine utilization history and the other with no history. Another factor to be verified is the degradation time of atrazine in different concentrations (recommended dose - DR, triple of DR and quintuple of DR), so a factorial planning was elaborated with three factors and two levels of variation and two repetitions in the point central. To determine the amount of carbon dioxide (CO2) released during the tests, which reflects the activity of the soil microorganism responsible for the degradation of organic compounds, the soil basal respiration technique was used. Another analysis was the Fourier Transform Infrared Spectroscopy (FTIR) in order to verify the nitrogen mineralization of the amine groups. And, to verify the degradation of atrazine throughout the experiment (beginning, 7, 14 and 63 days) the analysis of gas chromatography coupled to the mass spectrometer was carried out. The agricultural soil used in the experiment presented better results compared to the soil with no history of atrazine use. The maximum levels of yeast biomass produced better results in relation to the evolution variable of CO2. On the other hand, the maize straw factor had a milder effect, indicating that higher additions of this material may be related to the soil characteristics and, therefore, provide greater sorption of atrazine, with consequent lower bioavailability for degrading microorganisms. In all the tests performed the reduction of more than 55% of the levels of atrazine concentration occurred in the first seven days, and in eight of the trials, this reduction reached more than 72%. Thus, the results demonstrated that yeast biomass associated with corn straw has the potential to stimulate the degradation of atrazine in the soil.